Effect of Barrier Crops and Supplemented Pollen Rows on Natural Out Crossing in Chilli (Capsicum annuum L.) - RUMA DEVI; S.K. ARORA; J.S. KANWAR (Seed Research, 2026)
Parental lines of Chilli Hybrid-1 (CH 1) viz., male sterile line (MS-12; erect fruiting habit; recessive) and Ludhiana Local Selection (LSS; drooping fruiting habit; dominant) were used to find out the effect of barrier crops and additional pollen rows on the percentage out crossing for hybrid seed production in chilli during 1999-2001. The sterile plants of MS-12 were taken as seed parent and fertile plants as pollen parent wheras, LLS served as contaminator. In the first treatment, a crop barrier (Dhaincha and pearl millet) was provided between the hybrid seed production plot (HSPP) and contaminator plot (CP), whereas, in the second treatment five additional border rows of pollen parent were provided in the HSPP towards the CP. The land was kept fallow between two plots. The percentage out crossing was determined as per the fruiting habit in the next generation. Additional pollen rows and barrier crops plantation significantly reduced the natural out crossing to 1.55 per cent and 1.37 per cent respectively, than those of 14.05 per cent under control.